Correlation between hyperbilirubinemia risk and immune cell mitochondria parameters in neonates with jaundice - Wang, Yingying; Wang, Hongwei; Zhang, Qiang; Li, Shanshan; Mao, Yiping; Lu, Jiajin; Shen, Yeqin; Han, Yaping (Frontiers in Pediatrics, 2023)
Purpose: To explore the correlation between mitochondria parameters of immune cells and hyperbilirubinemia risk in hospitalized neonates with jaundice. Methods: This retrospective study included jaundiced neonates born between September 2020 and March 2022 at Shaoxing Keqiao Women & Children’s Hospital. The neonates were divided into low, intermediate-low, intermediate-high, and high-risk groups according to the hyperbilirubinemia risk. The purpose parameters including percentage, absolute count, mitochondrial mass (MM), and single-cell MM (SCMM) of peripheral blood T lymphocytes detected by flow cytometry were collected. Results: Finally, 162 neonates with jaundice (47, 41, 39, and 35 with low, intermediate-low, intermediate-high, and high-risk) were included. CD3+ SCMM was significantly higher in the high-risk group compared with the low and intermediate-low-risk groups (both P<0.0083), CD4+ SCMM was significantly higher in the high-risk group compared with the three other groups (all P<0.0083), and CD8+ SCMM was significantly higher in the intermediate-low and high-risk groups compared with the low-risk group (both P<0.0083). CD3+ (r=0.34, P<0.001) and CD4+ (r=0.20, P=0.010) SCMM positively correlated with bilirubin levels. Conclusions: The mitochondrial SCMM parameters differed significantly among jaundiced neonates with different hyperbilirubinemia risks. CD3+ and CD4+ T cell SCMM values were positively correlated with the serum bilirubin levels, and might correlated with hyperbilirubinemia risk.